Effect of Aging and Moisture Damage on Fatigue Cracking Properties in Asphalt Mixtures - Sung Lin Yang (MDPI AG, 2021)
Recently, damage to asphalt pavements in South Korea has increased because of direct and indirect factors caused by abnormal climatic changes, such as torrential rains, prolonged heatwaves in summer, and heavy snowfall in winter. Additionally, the use of medium and heavy vehicles is also a contributing factor. Therefore, an experimental procedure to study the moisture damage and fracture properties of asphalt pavements considering the recent changes in precipitation properties, deterioration of road pavement, and traffic conditions in South Korea was developed in this study. Additionally, changes in material properties according to the indoor aging process and fatigue crack resistance were evaluated for hot mix and warm mix asphalt mixtures of the same grade and different initial production and construction temperatures. To evaluate the effect of aging and moisture damage on fatigue cracking, the experimental coefficient values of the predictive model were calculated for each condition. It was observed that the material properties of hot mix asphalt mixtures changed with an increase in aging and moisture damage. The service life of the pavement was reduced by approximately 40–80% owing to moisture damage, whereas aging had a greater effect on fatigue life as the service life increased.